The Role of Organizational Culture in Mediating Decentralization of Decision Making and Management Information Systems on the Organizational Citizenship Behavior of Employees - Basrizal; Heryanto (Jurnal Informatika Ekonomi Bisnis, 2026)
This study aims to analyze the effect of decentralization of decision-making and management information systems on Organizational Citizenship Behavior with organizational culture as an intervening variable on employees of the Pesisir Bukit Sub-district Office in Sungai Penuh City. This study uses a quantitative approach with a survey method, where all employees were respondents with a sample size of 32 people. Data collection was carried out through questionnaires, while data analysis used validity and reliability tests, classical assumption tests, multiple linear regression analysis, and the Sobel test to examine the role of mediating variables. The results of the study indicate that decentralization of decision-making and management information systems have a positive and significant effect on organizational culture. In addition, decentralization of decision-making, management information systems, and organizational culture also have a positive and significant effect on Organizational Citizenship Behavior. The results of the Sobel test show that organizational culture is able to significantly mediate the effect of decentralization of decision-making on Organizational Citizenship Behavior, but is unable to significantly mediate the effect of management information systems on Organizational Citizenship Behavior. This finding indicates that the influence of management information systems on OCB is more dominantly direct, while decentralization of decision-making requires the role of organizational culture as a reinforcer. This research is expected to provide practical contributions to human resource management in the public sector and serve as a reference for further research.